A study on UHPLC-MS/MS analyses of DNA and RNA oxidative damage metabolites in patients with cervical carcinoma: 8-oxoG in urine as a potential biomarker of cervical carcinoma. Issue 4 (April 2022) - Lin, Rong-Rong; Li, Xiang-Yu; Weng, Qing-Hua; Zhou, Xing-Xing; Zheng, Fei-Yun; Cai, Jian-Ping
Abstract: Objective: The purpose of this study was to compare the levels of 8-oxoG and 8-oxodG in urine of patients with cervical carcinoma and healthy women to evaluate their influences on cervical carcinoma. Methods: In this study, urine samples were collected from 70 patients with cervical carcinoma, 24 patients with one-year follow-up, and 100 healthy women. The contents of 8-oxodG and 8-oxoG in urine were assayed by ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS). Results: The levels of 8-oxoG and 8-oxodG were higher in patients with cervical carcinoma (P < 0.000), while AUC of 8-oxoG and 8-oxodG was higher than 0.7. Specifically, the high-risk HPV (HR-HPV) positive group had higher 8-oxoG levels (P < 0.000), but there was no difference in 8-oxodG levels. Yet, 8-oxoG level was associated with lymphatic metastasis, lymph-vascular space infiltration (LVSI) and stromal infiltration, while 8-oxodG level was affected by the differentiation degree and stromal infiltration. According to statistics, the distinct cut-off index of lymphatic metastasis was 7.282 nmol/mmol creatinine. After operation, the concentrations of 8-oxoG and 8-oxodG dropped significantly (8-oxoG P < 0.000, 8-oxodG P = 0.004). Except for chemotherapy group, the urinary 8-oxoG dose of all treatment groups and 8-oxodG dose of chemo-radiotherapy group declined obviously. Conclusions: 8-oxoG may be a potential biomarker for cervical carcinoma. Abstract : 8-oxoG, oxidative damage, cervical carcinoma, UHPLC- MS/MS, urine, biomarker.